2012
DOI: 10.1002/jms.3109
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the intrinsic polar [4 + 2+] cycloaddition reactivity of gaseous carbosulfonium and carboxonium ions

Abstract: Gas-phase reactions of model carbosulfonium ions (CH(3)-S(+)=CH(2;) CH(3)CH(2)-S(+)=CH(2) and Ph-S(+)=CH(2)) and an O-analogue carboxonium ion (CH(3)-O(+)=CH(2)) with acyclic (isoprene, 1,3-butadiene, methyl vinyl ketone) and cyclic (1,3-cyclohexadiene, thiophene, furan) conjugated dienes were systematically investigated by pentaquadrupole mass spectrometry. As corroborated by B3LYP/6-311 G(d,p) calculations, the carbosulfonium ions first react at large extents with the dienes forming adducts via simple additi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2015
2015
2015
2015

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 68 publications
0
2
0
Order By: Relevance
“…To achieve C-C [9][10][11][12] or C-S [13][14][15][16][17][18][19][20] coupling involved in the ring closure process, activation of C-H, [9][10][11][12][13][14][15][16][17][18][19][20] C-X (X = Br or I) 15,18,20 or C-S 14,17 bonds is a prerequisite. While gas-phase investigations proved helpful to obtain mechanistic aspects for numerous processes, except for a few reports on the formation of sulfur heterocycles in the gas phase, 21 a more detailed understanding of the elementary steps is lacking.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…To achieve C-C [9][10][11][12] or C-S [13][14][15][16][17][18][19][20] coupling involved in the ring closure process, activation of C-H, [9][10][11][12][13][14][15][16][17][18][19][20] C-X (X = Br or I) 15,18,20 or C-S 14,17 bonds is a prerequisite. While gas-phase investigations proved helpful to obtain mechanistic aspects for numerous processes, except for a few reports on the formation of sulfur heterocycles in the gas phase, 21 a more detailed understanding of the elementary steps is lacking.…”
Section: Introductionmentioning
confidence: 99%
“…While gas-phase investigations proved helpful to obtain mechanistic aspects for numerous processes, except for a few reports on the formation of sulfur heterocycles in the gas phase, 21 a more detailed understanding of the elementary steps is lacking. In a previous study on the reactions of atomic Ln + with chlorobenzene, 22 strong indications have been found that Ho + generates efficiently the insertion product Ho(C 6 H 5 )(Cl) + which then promotes HCl elimination in a secondary reaction with chlorobenzene; further, intriguing coupling processes have been observed in preliminary studies on consecutive reactions of Ln + with chlorobenzene and thioanisole in which Ho + exhibited the highest efficiency.…”
Section: Introductionmentioning
confidence: 99%